(untitled) (Nepal Medical College Journal, 2019)
Pityriasis versicolor (PV) also known as Tinea versicolor is a benign, chronic superficial fungal infection of the skin caused by Malassezia furfur. It is characterized by dyspigmented macules with fine branny scales. The purpose of this study was to assess the epidemiological profile and clinical pattern of PV in a group of patients visiting a tertiary care centre of Nepal. A descriptive cross-sectional study was carried out including 150 patients diagnosed to have PV at the outpatient dermatology department of Nepal Medical College Teaching Hospital. Patients with the diagnosis of PV were included in the study. A detailed history was taken and it was followed by a thorough clinical examination. The findings of history and clinical examinations were documented in a predesigned proforma. Statistical Package for the Social Sciences (SPSS) version 16 was used to tabulate the data and analyze the results. There was a slight male preponderance with maximum patients of the age group 11 – 20 years. A majority of patients were students. Forty three (28.7%) patients had similar problem in close contacts and 42% had recurrent disease. Wearing of occlusive synthetic clothing was the commonest predisposing factor. Upper chest and upper back were the most involved sites. Hypopigmented macules were the commonest lesions in 72.7%. Coexisting seborrheic dermatitis (commonly pityriasis capitis ) was present in 44.67% of patients. Clinicoepidemiological profile of PV in our setting is similar to many studies done mostly in India. But few findings differ which indicates the need for further studies in Nepal especially from Terai regions where the prevalence is expected to be more.